Linking Corporate Social Responsibility (CSR) and organizational performance: The moderating effect of corporate reputation - Kuldeep Singh; Madhvendra Misra (European Research on Management and Business Economics (ERMBE), 2021)
The study empirically investigates the relationship between corporate social responsibility (CSR) andorganizational performance from the perspective of European multinational firms. Further, the studyexamines the effectiveness of corporate reputation as a moderator on CSR-organizational performancelinkages. Final data comprised 340 responses collected from senior executives/managers working in Euro-pean multinational firms. A two-stage approach was used to analyze the association: stage 1 involvedtheoretical model construction using the strategic paradigm of literature; in stage 2, hierarchical regres-sion analysis was performed to examine the relevant relationships. Results have shown that CSR, whenexercised towards external stakeholders, influences organizational performance. Moreover, this influ-ence has been found to vary between well-established, reputable firms and business firms with weakerreputations.
Keywords: L25; M14; 650; Corporate Social Responsibility; Organizational Performance; Corporate Reputation